Genealogia do Ensino Secundário Unificado: Uma nova matriz social - Rui Gomes Machado (Universidade do Minho, 2001)
Our main thesis about the origin of the Portuguese comprehensive school claims that it emerges from the new place of Portugal in the world system and from the new problems of education governance. Its implementation cant be understood as a manifestation of an underlying principle of democracy and equality of government or as a struggle of a collective subject or popular resistance that takes charge of its equal formation. Those ideological discourses play a role in the institutional integration of the model, but as legitimation and external validation, though its need as government technology of social demands was expressed a long time ago. However, the conditions of rationality and the technologies that allow it was a scarce resource. Those conditions gradually emerges during the analysed period (1974-1991).